Prinsip Pelayanan Kerohanian di Penjara - Pieter, Roy (STT KINGDOM BALI, 2024)
Spiritual ministry in prison is a service that is devoted to spiritually serving people who are imprisoned for being involved in criminal cases that violate the law so that they are placed in a correctional institution (prison) to serve their sentence. The active role of the Church as the Body of Christ on earth is very necessary in living the preaching of the Gospel which is mandated by Christ as the head of the Church, especially serving marginal groups, namely prisoners. The form of concrete services provided is certainly inseparable from the church's tri-duties, namely Kainonia, Marturia and Diakonia. This research is limited to the work of Marturia and the church's Diakonia for prisoners in prison. The purpose of this study seeks to explore in the literature the nature and forms of spiritual ministry in prisons. This research method uses the literature study method